From research and living lab to implementation of C-ITS - Jandrisits, Marko; Harrer, Manfred; Kraschl-Hirschmann, Karin; Paier, Alexander; Alcaraz, Gonzalo (Elektrotechnik und Informationstechnik, 2015)
A new technology for a further improved future. Who is the acting subject? Key actors in this ECo-AT Living Lab do the preparation jointly together; this is unusual and the newest trend. No commercial structure, no traditional valley of death-type deployment pitfall. Asfinag, Kapsch, Siemens, Swarco and an entire ECo-AT consortium are setting the scene for Europe’s test of the latest C-ITS technology. And, because all this is embedded within an international corridor Rotterdam–Frankfurt/M.–Vienna, this Living Lab approach is evolving to a new instrument for preparing C-ITS deployment.